On the Effects of COVID-19 Safer-At-Home Policies on Social Distancing, Car Crashes and Pollution - Abel Brodeur; Nikolai Cook; Taylor Wright (Global Labor Organization (GLO), 2021)
This paper investigates the impacts of COVID-19 safer-at-home polices on collisions and pollution. We find that statewide safer-at-home policies lead to a 20% reduction in vehicular collisions and that the effect is entirely driven by less severe collisions. For pollution, we find particulate matter concentration levels approximately 1.5µg/m3 lower during the period of a safer-at-home order, representing a 25% reduction. We document a similar reduction in air pollution following the implementation of similar policies in Europe. We calculate that as of the end of June 2020, the benefits from avoided car collisions in the U.S. were approximately 16 billion while the benefits from reduced air pollution could be as high as 13 billion.
Keywords: P48; Q53; Q58; 330; COVID-19; safer-at-home; lockdowns; air pollution; car crashes